1989
DOI: 10.1002/1097-0142(19890801)64:3<598::aid-cncr2820640306>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of diet, lifestyle, and prostate cancer in adventist men

Abstract: Dietary and lifestyle characteristics were evaluated in relation to subsequent prostatic cancer risk in a cohort of approximately 14,000 Seventh-day Adventist men who completed a detailed lifestyle questionnaire in 1976 and who were monitored for cancer incidence until the end of 1982. During the 6-year follow-up period, 180 histologically confirmed prostatic cancers were detected among some 78,000 man-years of follow-up. Increasing educational attainment was associated with significantly decreased risk of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
306
1
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(337 citation statements)
references
References 24 publications
16
306
1
14
Order By: Relevance
“…Our non‐significant associations between several vegetable subtypes and risk of prostate cancer are in line with previous prospective studies which have also found no association between overall prostate cancer risk and cruciferous9, 12, 27 or leafy vegetable intake 8, 9, 28, 29. Also, although early reports linked frequent consumption of tomatoes, tomato products or lycopene (a carotenoid from tomatoes) with lower risk of overall prostate cancer,13, 25 our study and the latest meta‐analysis from WCRF/AICR did not support this association,3 and nor did findings from a pooled analysis of blood lycopene concentrations and overall prostate cancer risk (although there was statistically significant heterogeneity by stage of disease, and the odds ratios (ORs) for aggressive disease for the highest compared with the lowest fifth of lycopene was 0.65 (95% CI: 0.46, 0.91; p‐ trend = 0.032) 26. However, it should be highlighted that not all studies have divided fruit and vegetable intake in the same subtypes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our non‐significant associations between several vegetable subtypes and risk of prostate cancer are in line with previous prospective studies which have also found no association between overall prostate cancer risk and cruciferous9, 12, 27 or leafy vegetable intake 8, 9, 28, 29. Also, although early reports linked frequent consumption of tomatoes, tomato products or lycopene (a carotenoid from tomatoes) with lower risk of overall prostate cancer,13, 25 our study and the latest meta‐analysis from WCRF/AICR did not support this association,3 and nor did findings from a pooled analysis of blood lycopene concentrations and overall prostate cancer risk (although there was statistically significant heterogeneity by stage of disease, and the odds ratios (ORs) for aggressive disease for the highest compared with the lowest fifth of lycopene was 0.65 (95% CI: 0.46, 0.91; p‐ trend = 0.032) 26. However, it should be highlighted that not all studies have divided fruit and vegetable intake in the same subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…Only one24 out of the five5, 8, 9, 24, 25 studies that have assessed the association between citrus fruit and prostate cancer risk has also found a significant inverse association, and no association between circulating concentrations of the citrus biomarker β ‐cryptoxanthin and prostate cancer risk was observed in a pooled analysis of 10 prospective studies 26. Our non‐significant associations between several vegetable subtypes and risk of prostate cancer are in line with previous prospective studies which have also found no association between overall prostate cancer risk and cruciferous9, 12, 27 or leafy vegetable intake 8, 9, 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, of the seven studies that specifically examined whether dietary tomato products in particular reduce the risk of prostate cancer, only three found this to be the case. 5,84,85 One further is inconclusive statistically but tends to support that hypothesis 86 and three found no association at all. 73,87,88 However, one of the latter three negative studies 73 did describe a strong dietary association of decreased risk of prostate cancer with the consumption of tinned baked beans (RR ¼ 0.52; 95% confidence interval ¼ 0.31 -0.88) and the authors did suggest that tinned baked beans do provide a large amount of highly bioavailable lycopene.…”
Section: Lycopene and Prostate Cancermentioning
confidence: 91%
“…Old epidemiological evidence of the role of nut consumption on cancer incidence was inconclusive [57,58,59]. More recent reports support a preventive role, although limited to women [56,57,58,59]. A small case-control study in Greek women [60] suggests that a diet rich in nuts, seeds and pulses reduces the risk of endometrial cancer by 27% compared to infrequent consumption of such foods.…”
Section: Epidemiological Studies Of Nut Consumption and Health Outmentioning
confidence: 99%